APEX1 regulates alternative splicing of key tumorigenesis genes in non-small-cell lung cancer - Li Peng; Yuwei Liu; Jing Chen; Mengxin Cheng; Ying Wu; Min Chen; Ya Zhong; Dan Shen; Ling Chen; Xujun Ye (BMC, 2022)
Abstract Background Aberrant alternative splicing (AS) contributes to tumor progression. Previous studies have shown that apurinic-apyrimidinic endonuclease-1 (APEX1) is involved in tumor progression. It is unknown whether APEX1 functions in tumor progression by regulation of AS. It is also unknown whether APEX1 can regulate non-small-cell lung cancer (NSCLC) proliferation and apoptosis. We analyzed APEX1 expression levels in 517 lung NSCLC samples from the TCGA (Cancer Genome Atlas) database. The impact of APEX1 over expression on A549 cell proliferation and apoptosis was detected by the methyl thiazolyl tetrazolium assay and by flow cytometry. The transcriptome of A549 cells with and without APEX1 over expression was determined by Illumina sequencing, followed by analysis of AS. RT-qPCR validated expression of APEX1-related genes in A549 cells. We have successfully applied RNA-seq technology to demonstrate APEX1 regulation of AS. Results APEX1 expression was shown to be upregulated in NSCLC samples and to reduce cell proliferation and induce apoptosis of A549 cells. In addition, APEX1 regulated AS of key tumorigenesis genes involved in cancer proliferation and apoptosis within MAPK and Wnt signaling pathways. Each of these pathways are involved in lung cancer progression. Furthermore, validated AS events regulated by APEX1 were in key tumorigenesis genes; AXIN1 (axis inhibition protein 1), GCNT2 (N-acetyl glucosaminyl transferase 2), and SMAD3 (SMAD Family Member 3). These genes encode signaling pathway transcription regulatory factors. Conclusions We found that increased expression of APEX1 was an independent prognostic factor related to NSCLC progression. Therefore, APEX1 regulation of AS may serve as a molecular marker or therapeutic target for NSCLC treatment.